Differential lncRNA expression profiles reveal the potential roles of lncRNAs in antiviral immune response of Crassostrea gigas. Issue 81 (October 2018) - Sun, Weiming; Feng, Jixing
Abstract: Long noncoding RNAs (lncRNAs) may play widespread roles in various biological processes. However, systematic profiles of lncRNAs in the biological responses of Pacific Oyster ( Crassostrea gigas ) to pathogen infection have not yet been demonstrated. Here, we have conducted an exhaustive comparative transcriptome analysis using a bioinformatics approach to exam the functions of lncRNAs response to Ostreid herpesvirus 1μVar (OsHV-1μVar) challenge. In total, 101 differentially expressed lncRNAs (DE-lncRNA) during OsHV-1μVar infections were identified. Compared with differentially expressed mRNAs (DE-mRNA), DE-lncRNAs are shorter in terms of overall length but longer in terms of exon length. These lncRNAs shared similar characteristics with previously reported invertebrate lncRNAs, such as relatively low GC content, low exon number and low sequence conservation, but low expression level were not observed. 20 DE-lncRNAs are typically co-expressed with their neighboring genes annotated as GO terms (GO: 0044237), indicating that these lncRNAs are involved in binding and cellular process functions in cis mode. The weighted gene co-expression network (WGCNA) analysis resulted in 15 modules. The highlighted blue module was specifically demonstrated a co-expression relationship between 14 DE-lncRNAs and 17 immune-related DE-mRNAs (IR-DE-mRNA). Three hub lncRNAs within this module were co-expressed with one hub IR-DE-mRNA involved in fibrinogen-related protein. It was speculated that lncRNAs is extensively involved in oyster antiviral innate immune system. The present study will facilitate subsequently experimental studies to unravel the function of lncRNAs in marine invertebrate response to pathogen infection. Highlights: 101 differentially expressed lncRNAs during Ostreid herpesvirus infection were identified. LncRNAs are expressed in a time-dependent manner during viral challenge. LncRNAs may play a role in binding and cellular process functions in cis mode. 14 lncRNAs regulate the expression of 17 antiviral immune-related mRNAs.